Innovation network in the Portuguese textile and clothing industry - Carvalho, João (2018)
Innovating consists on doing something different or developing new input aggregations, with the goal of achieving a better solution than the current one. The ability to create new knowledge depends on the exploration of complementary skills, which might be internal or external to the operation, reflecting the changes that the organizations have been making in their management style and their relations with other economic agents. Successful innovation results from an interactive learning process between users and producers, between competitors, customers or suppliers and other knowledge and training institutions, such as universities and higher education institutions, or R&D centers.This research aims to contribute to the theme of innovation networks in the Textile and Clothing Industry (TCI) of Portuguese companies by exploring who are the different partners of the existing innovation networks in the Portuguese TCI. A survey with 86 companies suggests that Portuguese TCI companies are preferentially focused on product innovations and process innovations, with customers and suppliers as preferred partners. Therefore, vertical cooperation with suppliers and customers plays a greater role in business innovation of Portuguese TCI companies compared to horizontal cooperation with research centers, universities and technological centers.